2017
DOI: 10.12957/demetra.2017.22559
|View full text |Cite
|
Sign up to set email alerts
|

Cuerpo Y Percepción en Una Zona Rural De México: ¿una Preocupación Solo De Mujeres O También De Hombres?

Abstract: Cuerpo y percepción en una zona rural de México: ¿una preocupación solo de mujeres o también de hombres?Body perception in a rural area of Mexico: is there a concern only women or also men?Resumen Introducción: El presente estudio se inscribe en los trabajos de alimentación y género, entre los cuales se ve al cuerpo como un constructo social. La preocupación por el cuerpo, la imagen corporal y la alimentación se ha convertido actualmente en un problema, sobre todo para las mujeres urbanas. Sin embargo, se sabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…25 When results are compared, in relation to the level of body image dissatisfaction, with those obtained in populations from urban areas, it be seen that there is no significant variation and that the tendency to thinness is shared by both contexts, for example, in a study carried out in three Chinese communities, one of them rural, it was found that the participants from the three communities had a desire for a slimmer figure in addition to sharing the concern about the consumption of fats, which is why the researchers mention that those are phenomena more related to modernity than to ethnicity. 35 An important aspect to consider is the inclusion of both genders in the study samples, allowing the possibility of finding that body dissatisfaction is a phenomenon shared by men, who may even be presenting a higher level of dissatisfaction than women, 24,37 a similar situation presented in urbanized areas. 41,42 The inclusion of men in the study samples becomes even more important when considering that body dissatisfaction is a risk factor for eating disorders, a growing public health problem: according to data from the Center for Health and Social Care (NHS) in the United Kingdom, between 2005 and 2014 the number of hospital admissions due to eating disorders in men aged 10-24 increased by 20%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 When results are compared, in relation to the level of body image dissatisfaction, with those obtained in populations from urban areas, it be seen that there is no significant variation and that the tendency to thinness is shared by both contexts, for example, in a study carried out in three Chinese communities, one of them rural, it was found that the participants from the three communities had a desire for a slimmer figure in addition to sharing the concern about the consumption of fats, which is why the researchers mention that those are phenomena more related to modernity than to ethnicity. 35 An important aspect to consider is the inclusion of both genders in the study samples, allowing the possibility of finding that body dissatisfaction is a phenomenon shared by men, who may even be presenting a higher level of dissatisfaction than women, 24,37 a similar situation presented in urbanized areas. 41,42 The inclusion of men in the study samples becomes even more important when considering that body dissatisfaction is a risk factor for eating disorders, a growing public health problem: according to data from the Center for Health and Social Care (NHS) in the United Kingdom, between 2005 and 2014 the number of hospital admissions due to eating disorders in men aged 10-24 increased by 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender, in works that included both sexes, women reported higher levels of dissatisfaction with body image; except for two studies 24,37 in which it was men who reported higher levels of dissatisfaction.…”
Section: %mentioning
confidence: 97%
See 1 more Smart Citation